INNOVATING SUSTAINABLE MOBILITY: SPATIAL ZONING AND DIGITAL INTEGRATION IN BALI'S HIGH-DENSITY DESTINATIONS - Semara, I Made Trisna; Sutiarso, Moh Agus (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Bali's exponential tourism growth has triggered chronic traffic congestion, exacerbated by a severe imbalance between vehicle volume and road capacity in high-density areas. This study proposes and evaluates the Tourism Mobility Zoning System (TMZS) integrated with digital navigation technology as a systemic spatial solution. A mixed-method approach was employed, utilizing Simple Linear Regression on secondary macro-data (2011-2024) to empirically justify the urgency of mobility interventions, alongside thematic analysis of field observations, document studies, and in-depth interviews in Kuta, Sanur, and Ubud. The findings indicate that TMZS effectively regulates tourist flows by categorizing destinations into four functional zones: Transit-Oriented, Car-Free, Pedestrian, and Limited Transport. Furthermore, the conceptual integration of TMZS with a real-time digital application (ZonaFlow) optimizes parking management and multi-modal transit efficiency. As a theoretical novelty, this research bridges spatial zoning frameworks with digital technology, extending carrying capacity and Transit-Oriented Development (TOD) theories into a novel socio-spatial model tailored for island tourism. Practically, the study urges policymakers to formally adopt TMZS into regional spatial plans, supported by targeted investments in transit hubs and strict law enforcement, thereby facilitating a sustainable transition from private vehicle reliance.